The crisis of classical music in America : lessons from a life in the education of musicians - Freeman, Robert (Lanham, Maryland : Rowman & Littlefield, 2014)
"The crisis of classical music in America focuses on solutions for the oversupply of classically trained musicians in America, a problem that grows ever more chronic as opportunities for classical musicians to gain full-time employment diminish. An acute observer of the professional music scene, Robert Freeman describes how this problem has no chance of abating unless music schools equip students with the communication and analytical skills they need to succeed in the rapidly changing landscape for America's music professionals. The book maps a broad range of reforms required in the field of advanced music education and the organizations responsible for that education."
The winds of change -- Where did musical instruction come from? -- My own education -- Advice for parents : should your child learn to play the cello? -- Advice for collegiate music students : how best to fulfill your dreams -- Advice for collegiate music faculty : should all your students aim at Carnegie Hall? Should all your students teach at Harvard? -- Advice for music deans : building educational programs for the new century -- Advice for provosts and presidents : leadership for the music school of the future -- Some suggestions for foundation directors and for the national endowments for the arts and humanities : how to work at increasing demand -- Epilogue -- Appendix A. How to evaluate music faculty -- Appendix B. Convocation address by Robert Freeman.
Includes bibliographical references and index.
Keywords: Music -- Instruction and study -- United States; Music in universities and colleges -- United States